2010
DOI: 10.1002/ange.201002501
|View full text |Cite
|
Sign up to set email alerts
|

Pd Adatom Decorated (100) Preferentially Oriented Pt Nanoparticles for Formic Acid Electrooxidation

Abstract: Mehr als nur dekorativ: Mit Pd‐Adatomen dekorierte Pt‐Nanopartikel, die eine bevorzugte (100)‐Orientierung aufweisen, zeigen eine verbesserte Leistung bei der elektrokatalytischen Oxidation von Ameisensäure (siehe Schema). Da außerdem die Adatome auf eine ähnliche Weise abgeschieden werden wie bei analogen Einkristallstudien, können Vergleiche zwischen Einkristall‐ und Nanopartikelkatalyse angestellt werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 35 publications
0
6
1
Order By: Relevance
“…investigated the oxidation of formic acid and glycerol in alkaline and acidic environments using a Pd‐modified Pt electrode compared to monometallic catalysts. They found that the combined catalysts lower the onset potential for electrooxidation, and poisoning species are easily removed from the electrode surface, resulting in enhanced formic acid and glycerol oxidation [35,40,41] . This synergistic effect was also demonstrated for PtRu‐ and PdRu‐based catalysts [31,42,43] .…”
Section: Resultsmentioning
confidence: 89%
“…investigated the oxidation of formic acid and glycerol in alkaline and acidic environments using a Pd‐modified Pt electrode compared to monometallic catalysts. They found that the combined catalysts lower the onset potential for electrooxidation, and poisoning species are easily removed from the electrode surface, resulting in enhanced formic acid and glycerol oxidation [35,40,41] . This synergistic effect was also demonstrated for PtRu‐ and PdRu‐based catalysts [31,42,43] .…”
Section: Resultsmentioning
confidence: 89%
“…These studies evidenced the same structural electrocatalytic dependence, related to the presence of facets with (100) and (111) symmetries, as that observed with the model Pt surfaces. Additionally, to enhance the activity and/or to overcome the poisoning effect, the shaped Pt nanocrystals were also decorated with adatoms such as Pd, 64 Bi, 65,46 or Sb. 66 However, in these studies, the particle size of the samples (about 10 nm) is still too large from a practical point of view.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…This effect can be achieved by deposition of the metal monatomic layers on foreign metallic surfaces. Deposition of metal overlayers on well-defined surfaces and the resulting systems’ catalytic activities become a subject of numerous electrocatalytic and surface studies. Geometric and electronic modifications of pseudomorphic Pd overlayers affect both CO and hydrogen adsorption. , Obviously deposited monolayers differ in the dependence of the surface defects density. , Differences occur mainly at the oxide region, CO-stripping experiments and also at Pd UPD peaks during deposition. , However, the degree of modifications of catalytic properties of such surfaces is rather limited since the lattice constant characteristic for bulk material is promptly reconstructed with consecutive overlayers, generally, as early as in the second layer. The chemical influence of the background material is also much weaker for thicker deposits. Recently, it has been shown that the unique catalytic properties can be achieved by preparation of near-surface alloys (NSA’s) .…”
Section: Introductionmentioning
confidence: 99%